2020
DOI: 10.1007/s10548-020-00796-z
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Topography of Lower Urinary Tract Sensory Evoked Potentials

Abstract: Impaired lower urinary tract (LUT) afferents often cause LUT symptoms. Assessment of LUT afferent pathways is possible using bipolar cortical sensory evoked potential (SEP) recordings with the active electrode at the vertex during electrical stimulation in the LUT. This study aimed to investigate the topographical distribution and microstates of lower urinary tract sensory evoked potentials (LUTSEPs) using different stimulation frequencies. Ninety healthy subjects (18–36 years old, 40 women) were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This 'electrosensation' can be measured in the cerebral cortex by several methods, e.g., by measuring somatosensory evoked potentials (SSEP) [65] and by obtaining a magnetoencephalogram [66] by electrical stimulation of the LUT. Electrosensation was first described in experimental animals [67] and then it was applied in humans.…”
Section: Electrosensation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This 'electrosensation' can be measured in the cerebral cortex by several methods, e.g., by measuring somatosensory evoked potentials (SSEP) [65] and by obtaining a magnetoencephalogram [66] by electrical stimulation of the LUT. Electrosensation was first described in experimental animals [67] and then it was applied in humans.…”
Section: Electrosensation Studiesmentioning
confidence: 99%
“…[68] The area where evoked potentials are recorded are just around the medial motor cortex (Brodmann's Area 4) where the feet and viscera are located [66]. Recent SSEP studies compared the LUT stimulation frequencies by 0.5, 1.1, and 1.6 Hz, and showed that the lower the stimulation frequency was, the better the map strength might be, like CPT [65]. In contrast to electrical stimulation of the nerves innervating limbs, evoked responses from the thalamus are not clearly obtained by electrical stimulation in the LUT.…”
Section: Electrosensation Studiesmentioning
confidence: 99%